Cellular nutrient utilization and cancer - Montrose, David C.; Galluzzi, Lorenzo (International review of cell and molecular biology, 2019)
Cellular Nutrient Utilization and Cancer, Volume 347 in the International Review of Cell and Molecular Biology (IRCMB) series maintains a high standard by publishing invited articles on timely topics that are authored by prominent cell and molecular biologists. Sections in this new release include Sulfur metabolism and cancer, The interplay of genetic drivers of cancer and cellular nutrients to support oncogenesis, The diet's impact on nutrient availability for cancer cells, Nutrients as determinants of redox balance in cancer, The role of dietary lipids in colon cancer pathogenesis, The influence of diet on nutrient utilization by cancer cells and immune-surveillance, and more. --